Factors related to positive and negative attitudes toward dreams: an empirical investigation - Schredl, Michael (International journal of dream research, 2020)
Attitudes toward dreams can be positive, e.g., “I think that dreaming is in general a very interesting phenomenon” or negative, e.g., “Dreams are boring for me”. At first, research treated positive and negative attitudes toward dream as two poles of a unidimensional concept but recent evidence has suggested that despite the large overlap both concepts can be differentiated. The findings of the present online survey (N = 1450) supported this notion as variables like age, dream recall frequency, neuroticism, agreeableness are differentially associated with positive and negative attitudes towards dreams. Dream recall frequency and neuroticism were more closely related to positive attitudes toward dreams, whereas low agreeableness was more closely associated with negative attitudes toward dreams. Overall, the correlations between attitude towards dreams and stable factors like personality dimensions raise the question as to how and when attitudes towards dreams are formed, i.e., longitudinal studies during childhood, adolescence, and young adulthood would be desirable.